“A Palace for the Maize”: The Granary of Granaditas in Guanajuato and Neoclassical Civic Architecture in Colonial Mexico - Gordo Peláez, Luis (RACAR : Revue d'art canadienne / Canadian Art Review)

(untitled) (UAAC-AAUC (University Art Association of Canada | Association d'art des universités du Canada), 2013)
Construction of the new granary or alhóndiga in the Mexican city of Guanajuato began in the winter of 1798. Promoted by Intendant Juan Antonio de Riaño, this building would became a singular example of civic architecture, of Neoclassicism, and of buen gusto (good taste) in late-eighteenth-century Mexico. The history of this strong and beautiful building, with “nothing superfluous” in the words of the famous architect Manuel Tolsá, involves some of the most talented and distinguished characters of late Colonial Mexico, including Viceroys Branciforte and Iturrigaray, Intendant Riaño, and architects Juan de Dios de Trinidad Pérez, Francisco Ortiz de Castro, and José del Mazo y Avilés. Though this larger and better-equipped granary was clearly needed, its construction raised some controversy, particularly among those who considered it a tremendous expenditure for the city that was in need of other infrastructure and civic architecture. Juan Vicente Alamán, former alderman of the city of Guanajuato, expressed his noticeable disagreement with this monumental building, which he described as a “palace for the maize.”